Bio-oil synthesis from Botryococcus braunii by microwave-assisted pyrolysis - Ortiz, Edixon Daniel; Cahyono, Rochim Bakti; Budiman, Arief (Jurnal Rekayasa Proses, 2022)
Microalgae have proven to be a promising resource in renewable energy search; Products such as bio-oils could contribute to the replacement of petroleum. The objective of this investigation is to determine the decomposition mechanism, obtain the kinetic reaction, as well as evaluate the potential to obtain microalgae bio-oil through microwave-assisted pyrolysis (MAP). MAP is a new thermochemical conversion from biomass to bio-oil that is faster, efficient, controllable, and flexible, compared to conventional pyrolysis, rapid pyrolysis, or instant pyrolysis. As raw material in this experiment, Indonesian microalgae, Botryococcus braunii was used. The investigation focused on the temperature effect (100-300 °C) and the residence time (10-30 min); a modified microwave oven was used with a power of 900 W. Hexane was used for the extraction of bio- oil. The bio-oil composition was measured with chromatography of mass spectrometry gas (GC-MS) and then this data was used to evaluate a kinetic model and calculate the constant kinetic reaction of the pyrolysis process. The results indicated that bio-oil production begins from 100 °C, however, temperatures between 200-250 °C favor the production of bio-oil, while temperatures above 250 °C and the long residence times prioritize the production of bio-gas. Regarding the kinetic evaluated, the reactions seem to show from third to sixth order with an activation energy (E) of around 30 kj/mol and a pre-exponential factor (ln A) of around 9 s-1. Based on GC-MS Analysis, the bio-oil contains short chain alkanes, cycloalkanes, organic acids as well as aromatic, phenol, benzene compounds. On the other hand, although small amounts of oil were achieved, the decomposition of biomass was up to 50% favoring gas production, these results indicate that MAP has potential in the obtaining of biofuels such as bio-gas and bio-oil.